The role of fluoroquinolone-induced bacterial stress responses in the development of antimicrobial resistance - Brand, Chanté (Stellenbosch University, 2025)
Introduction: In response to quinolone-induced DNA damage, bacteria induce the SOS response to repair the damage, which can lead to development of antimicrobial resistance (AMR) via increased mutagenesis. N-acetyl-cysteine (NAC) has been demonstrated to suppress the ciprofloxacin (CIP)-induced SOS response and thereby mutagenesis in laboratory strains of Escherichia coli. Antibiotic-induced stress responses and their role in the development of AMR are not well studied in Klebsiella pneumoniae, which is known for high AMR rates, or in bacterial communities. This study described the role of CIP-induced stress responses in the development of AMR in susceptible E. coli and K. pneumoniae in single and mixed-species culture, and in quinolone (QN)-resistant isolates in single culture, and the effect of their suppression by NAC. Methods: Three susceptible (including one laboratory strain) and three quinolone (QN)-resistant clinical strains of E. coli and K. pneumoniae each were exposed to 0.5× their CIP minimum inhibitory concentrations (MIC), and to CIP in combination with 1 mg/ml NAC. For the coculture experiments, five combinations of susceptible strains of E. coli and K. pneumoniae were exposed to 0.5× CIP MIC of the E. coli isolates. Treatments were added after 2h of growth and gene expression was analysed after 4h of exposure using RNA-sequencing. Mutation rates were determined at 24h on media supplemented with 8× nalidixic acid (NA) MIC for susceptible strains, 2× CIP MIC for resistant strains, and 8× the NA MIC of each species for the co-cultures. Antibiotic-free controls were included in all experiments. Results: Upon CIP treatment of the susceptible strains, induction of the SOS response was seen in the E. coli laboratory strain (ECA; 7 genes), with larger induction of SOS (25-30 genes) and other stress responses in the susceptible K. pneumoniae isolates. SOS induction was also observed upon CIP exposure in two QN-resistant E. coli (5 and 14 genes) and one QNresistant K. pneumoniae (1 gene). One QN-resistant E. coli and all three susceptible and one QN-resistant K. pneumoniae demonstrated increased mutation rates after exposure to CIP. NAC reduced expression of SOS and other stress response genes compared to CIPexposed cultures in all isolates, and reduced mutation rates in most cases. In co-culture, susceptible E. coli induced SOS responses more strongly than in single culture (19 genes for ECA and 1-3 genes for the clinical isolates), however, the K. pneumoniae isolates demonstrated smaller inductions (3-6 genes). Increased mutation rates were not observed upon CIP exposure in co-culture, however, NAC reduced mutation rates compared to CIP- or unexposed K. pneumoniae clinical isolates and reduced the expression of SOS response genes. Discussion and conclusions: Induction of SOS and other stress responses, and mutagenesis, by sub-inhibitory CIP exposure was greater in susceptible K. pneumoniae isolates than E. coli, and was induced in some QN-resistant isolates. SOS responses were more strongly induced in susceptible E. coli isolates in co-culture than in single culture, and were induced in susceptible K. pneumoniae in co-culture despite the very low CIP concentrations. The potential of NAC to reduce SOS induction and mutagenesis mediated by CIP, even in resistant isolates, is promising and warrants further investigation as a strategy to reduce AMR.